Unpublished studies in a palliative care systematic review: a case study. Issue 3 (1st September 2016) - Vickerstaff, Victoria; Jones, Louise; Larkin, Philip; Stone, Paddy; Candy, Bridget
Abstract : Introduction: Published literature provides only limited and possibly selective knowledge (Chan et al ., 2014; Ionnidis, 2014). We are updating a Cochrane systematic review on mu-opioids antagonistic for bowel dysfunction in palliative and cancer patients in which we hope to include all relevant literature, including unpublished results. We have identified several trials where it is not known whether the study has been completed and/or whether the results are available. Including the results from these unpublished studies is in the interest of patients, doctors and the pharmaceutical industry. Furthermore, it is an important ethical issue. Aim: To obtain unpublished results. Methods: We sought contact with the authors and trial sponsors for the 13 trials we identified with no published data. We also searched regulatory drug reports of these trials. Results: Two of the six drug companies approached responded to our letter. After inspecting the review protocol, one company stated that they were unable to give us the requested information as they disagreed with our choice of participants. A second company agreed to meet to discuss their work. They directed us to a relevant poster available on the company website and stated that they planned to write-up the trial. Responses from authors of studies not sponsored by drug companies were easier to obtain. Conclusion: From trial registers and published protocols we have been able to identify many unpublished trials. Contacting the authors and companies is challenging. However, it is important to try to obtain unpublished trial reports to complete the evidence and reduce publication bias. References: Chan AW, Song F, Vickers A, et al . Increasing value and reducing waste: addressing inaccessible research. The Lancet 2014;383 (9913):257–266 Ioannidis JP. Clinical trials: what a waste. BMJ 2014;349 :7089